Body hydration levels and pH measurements of bath soap used among Tarumanagara University medical students: a cross sectional study - Raahiil Kusuma Maahirah; Linda Julianti Wijayadi (Explorer Front, 2025)
Background: The skin has an essential function of protecting the body against external environmental influences. The stratum corneum plays an important role in maintaining skin hydration and pH, which contribute to the skin barrier function. The normal pH of the skin ranges from 4.1 to 5.8, which affects the stability of the microbiome, the hydration of the stratum corneum, and the epidermal barrier function. The use of cleansing products, such as body wash, affects skin pH, where soaps with a high pH (10-11) can damage the stratum corneum lipid layer, leading to dryness, irritation, and decreased hydration levels. This study aims to describe skin hydration levels and pH of body wash used among Tarumanagara medical students class of 2023. Methods: This descriptive research design involved measuring skin hydration in various body areas using a corneometer and identifying the pH of body skin with a pH meter among medical students. Results: The results showed that the majority of subjects (68.1%) used soap with an alkaline pH (>8), with the highest prevalence in women compared to men. The right upper arm area showed the highest skin hydration, where 65.7% of subjects had very moist skin. The legs showed the lowest hydration, with 48.8% of subjects having very dry hydration. Conclusion: This study emphasizes the importance of using pH-balanced soap to support optimal skin hydration. Moisturizer use after bathing and increased mineral water consumption are also recommended to maintain skin hydration balance. The findings provide important insights to raise awareness of skincare habits that support holistic skin health.